STRATEGI PEMASARAN DI MASA PANDEMI COVID-19 UNTUK MENINGKATKAN PENJUALAN (STUDI KASUS UMKM DAPUR UMI DI DESA MUARA JAYA KABUPATEN LAMPUNG BARAT) - Lidya Rista Sela; Habiburrahman Habiburrahman (PENERBIT LAFADZ JAYA, 2022)
Dapur Umi is one of the small and medium sized micro enterprises positioned in Muara Jaya Village, West Lampung Regency. However taking benefit of the booklet of the COVID-19 pandemic has had a large effect on Dapur Umi enterprise continuity. Dapur Umi, which formerly opened a store close to an excessive college (SMA), is now pressured to shut because of the Covid pandemic, which has required anybody to live at domestic. But, Dapur Umi maintains to run his enterprise with continual use until now via promoting at domestic thru net. With online sales that Dapur Umi will undertake as an end result, they could retain to live on and reply higher to modifications within the enterprise weather, specifically throughout this Covid-19 pandemic. The reason of this remark is to discover the maximum suitable advertising methods carried out in Dapur Umi amid the Covid-19 pandemic and analyze the limitations Dapur Umi faces at some stage in the Covid-19 pandemic of this studies layout makes use of analytical techniques qualitatively. The outcomes of the examine display that for UMKM to live on, enterprise actors want to make enterprise choices, mainly in the discipline of marketing. The advertising method being f shed via Dapur Umi to sustain its business for the duration of the COVID-19 pandemic consists of product strategies, pricing techniques, merchandising tactics and placement processes. The obstacle for Dapur Umi to put into effect an advertising approach in order that it may live on at some point of the Covid-19 pandemic is the drop in clients because of the shortage of.